PH‐dependent disruption of Escherichia coli ATCC 25922 and model membranes by the human antimicrobial peptides hepcidin 20 and 25. (9th May 2013) - Maisetta, Giuseppantonio; Vitali, Alberto; Scorciapino, Mariano A.; Rinaldi, Andrea C.; Petruzzelli, Raffaele; Brancatisano, Franca L.; Esin, Semih; Stringaro, Annarita; Colone, Marisa; Luzi, Carla; Bozzi, Argante; Campa, Mario; et al.
Abstract : The human hepcidin 25 (hep‐25) and its isoform hepcidin 20 (hep‐20) are histidine‐containing, cystein rich, β‐sheet structured peptides endowed with antimicrobial activity. We previously reported that, similar to other histidine‐containing peptides, the microbicidal effects of hep‐25 and hep‐20 are highly enhanced at acidic pH. In the present study, we investigated whether pH influences the mode of action of hep‐25 and hep‐20 on Escherichia coli American Type Culture Collection 25922 and model membranes. A striking release of β‐galactosidase by hepcidin‐treated E. coli was observed at pH 5.0, whereas no inner membrane permeabilization capacity was seen at pH 7.4, even at bactericidal concentrations. Similar results were obtained by flow cytometry when assessing the internalization of propidium iodide by hepcidin‐treated E. coli . Scanning electron microscope imaging revealed that both peptides induced the formation of numerous blebs on the surface of bacterial cells at acidic pH but not at neutral pH. Moreover, a phospholipid/polydiacetylene colourimetric vesicle assay revealed a more evident membrane damaging effect at pH 5.0 than at pH 7.4. The leakage of entrapped dextrans of increasing molecular size from liposomes was also assessed at pH 7.4. Consistent with the lack of β‐galactosidase release from whole E. coli observed at such a pH value, evident leakage of only the smallest 4‐kDa dextran (and not of dextrans of 20 or 70 kDa) was observed, indicating a poor ability of hepcidin peptides to permeabilize liposome vesicles at pH 7.4. Altogether, the data obtained in the present study using different approaches strongly suggest that the ability of hepcidins to perturb bacterial membranes is markedly pH‐dependent. Abstract : The human hepcidin 25 (hep‐25) and its isoform hepcidin 20 (hep‐20) are histidine‐containing, cystein rich, β‐sheet structured peptides endowed with antimicrobial activity which is highly enhanced at acidic pH. The data obtained by using different approaches strongly suggested that the mode of hep‐25 and hep‐20 action and their ability to perturb Escherichia coli and model membranes is markedly pH‐dependent.